Prescribing pattern of analgesics used for postoperative pain and its correlate with patient and doctor satisfaction: - Patel, Prakruti P.; Gandhi, Ashay; Gandhi, Anuradha M.; K. Desai, Mira (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Post operative pain is difficult to assessment and its management has been neglected at times. Moreover, the drug treatment involves administration of drug on as and when basis which leads to inadequate control. Methods: This observational, prospective study was conducted in 100 post-operative patients i.e., 50 each from surgery and orthopedics departments. Investigator enrolled post-operative patients within 24 hours of surgery and followed them for next 5 days or till hospital discharge, whichever was earlier. Analgesic prescribing pattern, self-assessment of pain, patient and doctor satisfaction using ASSIST questionnaire were recorded in Case Record Form and analysed. Results: Out of 100 patients, average number of analgesics prescribed post-operatively was 1.49±0.5 (baseline and all follow-up). 76.5% patients received NSAIDs which included diclofenac (44.29%) and paracetamol (30.87%). Opioids in the form of tramadol were prescribed in 23.49% patients. Mean least pain experienced by patients on day 1 was 2±0.75 which decreased to 1.32±0.63 on day 5. Mean worst pain decreased from 6.64±1.43 on day 1 to 3.38±1.17 on day 5. Average percentage of duration of severe pain was 35.2%±16.48 on day 1 which successively decreased to 16.32±8.26 on day 5. Average pain relief observed in 62.3% patients on day one increased to 80.88% on day 5. Patient satisfaction increased as pain score decreased (r=-0.73) and a strong positive correlation was observed between doctor satisfaction and patient satisfaction (r=0.91). Conclusions: Inadequate control of post-operative pain affects effective patient management and recovery. Incorporation of effective pain assessment scores in pain management is desirable.